Researching in the age of Covid-19: - Kara, Helen; Khoo, Su-ming (Rapid response, 2020)
As researchers have begun to adapt to the continuing presence of COVID-19, they have also begun to reflect more deeply on fundamental research issues and assumptions. Researchers around the world have responded in diverse, thoughtful and creative ways - from adapting data collection methods to fostering researcher and community resilience, while also attending to often urgent needs for care. This book, part of a series of three Rapid Responses, connects themes of care and resilience, addressing their common concern with wellbeing. It has three parts: addressing researchers' wellbeing, considering participants' wellbeing, and exploring care and resilience as a shared and mutually entangled concern. The other two books focus on Response and Reassessment, and Creativity and Ethics. Together they help academic, applied and practitioner-researchers worldwide adapt to the new challenges COVID-19 brings.